Recent progress in the application of coconut and palm oil fibres in cement-based materials - Futami E.; Shafigh P.; Katman H.Y.B.; Ibrahim Z. (MDPI, 2023)
compressive strength; concrete; construction industry; construction material; detection method; sustainable development